An Analysis of Japanese Rituals of A new Geisha in Arthur Golden's Novel Memoirs of A Geisha - Eva Rachmayanti; Thathit Andini (University of Muhammadiyah Malang, 2014)
An Analysis of Japanese Rituals of A new Geisha in Arthur Golden's Novel Memoirs of A Geisha